Obowiązki wychowawcy klasy w szkołach średnich Drugiej Rzeczypospolitej - Kalinowska-Witek, Barbara (Biuletyn Historii Wychowania, 2014)
Educational influence is among the essential tasks of school activities. It should be performed by all the teachers and especially by form tutors. The modern model of the form tutor was formed during the interwar period. After Poland regained independence, it also gained the opportunity of creating its own schools and of conducting educational tasks in accordance with the needs of the country and the society. Educating the youth became one of the most important tasks. The duties of form tutors had to be redefined, too. The educational authorities issued the relevant regulations, which were popularised by educational magazines and introduced into schools under the guidance of school principals and teachers’ boards.